Myocardial deformation in malignant mitral valve prolapse: A shifting paradigm to dynamic mitral valve–ventricular interactions - Pace, Nathalie; Sellal, Jean-Marc; Venner, Clement; Mandry, Damien; Marie, Pierre-Yves; Filippetti, Laura; Echivard, Mathieu; Fraix, Antoine; Girerd, Nicolas; Lamiral, Zohra; De Chillou, Christian; Sadoul, Nicolas; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives: This study sought to assess the value of myocardial deformation using strain echocardiography in patients with mitral valve prolapse (MVP) and severe ventricular arrhythmia, and to evaluate its impact for rhythmic risk stratification. Background: MVP is a common valvular affection with an overly benign course. Unpredictably, selected patients will present a severe ventricular arrhythmia. Methods: Patients with MVP as the only cause of aborted SCD (MVP-aSCD: ventricular fibrillation, monomorphic and polymorphic ventricular tachycardia) with no other obvious reversible cause were identified. Non-consecutive patients referred for the echocardiographic evaluation of MVP were enrolled as a control cohort and dichotomized according to the presence of premature ventricular contractions (MVP-PVC) or absence (MVP-No PVC). All patients had a comprehensive strain assessment of mechanical dispersion (MD), post-systolic shortening and index (PSI). Results: A total of 260 patients were enrolled (20 MVP-aSCD, 54 MVP-PVC and 186 MVP-No PVC). Deformation patterns discrepancies were observed with higher PSI value in MVP-aSCD than in MVP-PVC (4.6  2.0 vs. 2.9  3.7, p=0.014) and higher MD value than in MVP-No PVC (46.0  13.0 vs. 36.4  10.8, p=0.002). Addition PSI and MD increased the prediction of severe ventricular arrhythmia on top of classical risk factors in MVP. Net reclassification improvement was 61% (p=0.008) for PSI and 71% (p=0.001) for MD. Conclusions: In MVP, myocardial deformation analysis with strain echocardiography identified specific contraction patterns with post-systolic shortening leading to increased value of PSI and MD translating the importance of mitral valve – myocardial interactions in the arrhythmogenesis of severe ventricular arrhythmia. Strain echocardiography may provide important implications for rhythmic risk stratification in MVP.